Marital Adjustment Model Based on Irrational Beliefs and Conflict Resolution Strategies Mediated by Cognitive Flexibility in Married Women - Ahmadi, Emad; Jafariroshan, Marjan; Basri, Ahmad (Iranian Journal of Neurodevelopmental Disorders, 2025)
Purpose: This study aimed to examine a structural model of marital adjustment based on irrational beliefs and conflict resolution strategies, with the mediating role of cognitive flexibility in married women. Methods and Materials: The research utilized a descriptive-correlational design based on structural equation modeling. The statistical population comprised married female university students aged 18–35 living in Tehran. A total of 456 participants were selected using convenience sampling according to inclusion criteria (e.g., marriage duration and parental status). Data were collected via online questionnaires including the Dyadic Adjustment Scale (Spanier, 1986), Irrational Beliefs Questionnaire (Jones, 1968), Conflict Tactics Scale (Straus et al., 1996), and the Cognitive Flexibility Inventory (Dennis & Vander Wal, 2010). SPSS version 21 and AMOS version 24 were used for data analysis. Descriptive statistics, Pearson correlation, and structural equation modeling (SEM) with maximum likelihood estimation were applied. Model fit was evaluated using indices such as χ²/df, GFI, AGFI, CFI, and RMSEA. Assumptions of normality and multicollinearity were checked using skewness, kurtosis, tolerance, and VIF values. Findings: The results indicated that irrational beliefs (β = −0.36, p < 0.001) and maladaptive conflict resolution strategies (β = −0.31, p < 0.001) were significant negative predictors of marital adjustment. Adaptive conflict resolution strategies showed a weaker but positive relationship (β = 0.12, p = 0.127). Cognitive flexibility mediated the effects of both irrational beliefs (β = −0.097, p < 0.001) and conflict resolution strategies (β = −0.094 to 0.077, p < 0.01) on marital adjustment. The model demonstrated acceptable fit indices (e.g., CFI = 0.962, RMSEA = 0.048), explaining 65% of the variance in marital adjustment. Conclusion: The findings underscore the central role of cognitive flexibility in enhancing marital adjustment by mitigating the negative effects of irrational beliefs and maladaptive conflict behaviors. Interventions targeting cognitive restructuring and flexibility training may improve relational outcomes in married women.